2012
DOI: 10.1093/ckj/sfs117
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in dengue virus infection

Abstract: BackgroundDengue is a growing public health problem in Pakistan and acute kidney injury (AKI) is one of the least studied complications of dengue virus infection (DVI). The aim of this study was to determine the frequency, severity and predictors of AKI in patients with DVI and to study the impact of AKI on the length of hospital stay and mortality.MethodsWe retrospectively reviewed medical records of patients aged ≥14 years hospitalized with a primary diagnosis of DVI at Aga Khan University Hospital Karachi b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 24 publications
11
65
4
2
Order By: Relevance
“…In this regard, when the AKIN classification was evaluated, the incidence of AKI ranged from 10.8% to 13.3%5 6 while, with CD, the incidence varied between 0.9% and 3.3% 3 4. We found two studies evaluating the incidence of AKI using the RIFLE criteria that reported a much higher incidence than our study 13 14.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…In this regard, when the AKIN classification was evaluated, the incidence of AKI ranged from 10.8% to 13.3%5 6 while, with CD, the incidence varied between 0.9% and 3.3% 3 4. We found two studies evaluating the incidence of AKI using the RIFLE criteria that reported a much higher incidence than our study 13 14.…”
Section: Discussioncontrasting
confidence: 46%
“…The probability of developing AKI in dengue infection varies from 0.9% to 13.3% according to the diagnostic criteria adopted and the severity of the dengue infection—that is, dengue fever (DF), dengue haemorrhagic fever (DHF) or dengue shock syndrome (DSS) 3–6. The reported incidence of AKI is 0.9%3 and 3.3%4 in DHF/DSS, while the incidence of AKI has been reported to be 10.8%5 and 13.3%6 in all types of dengue infection, irrespective of severity. The development of AKI has a significant impact on the outcome of patients with dengue infection, with mortality estimated at 11.3–64% and a longer hospital stay 3 4 6.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent finding that uses epithelial cells as the target cells for dengue virus also satisfy to the previous research that reported the increase of porcine renal cell line LLC-PK1 when exposed to TNF-α, one of the cytokine that released by epithelial cells in response to dengue infection [14]. The evidence of the increase of the permeability of monkey kidney in response to dengue infection as found in the recent study may help to explain why the mortality of dengue patients with acute kidney injury was higher than those without kidney injury as reported by previous researchs [15,16,17].…”
Section: Discussionsupporting
confidence: 70%